2021
DOI: 10.1021/acs.joc.0c03043
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Amorfrutins and Derivatives via Tandem Diels–Alder and Anionic Cascade Approaches

Abstract: We describe two complementary approaches based on a convergent [4+2] logic toward the synthesis of amorfrutins, cannabinoids, and related plant metabolites. An anionic cascade cyclization employing β-methoxycrotonates and β-chloro-α,βunsaturated esters yielded amorfrutins in four linear steps and demonstrated utility of β-alkoxycrotonate-derived nucleophiles as functional equivalents of β-ketoester-derived dianions. Analogously, tandem Diels−Alder/retro-Diels−Alder cycloaddition of dimedone-derived bis(trimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Like for CBC, the most recent synthetic procedures for preparing CBG have been reported in the year 2021. The group of Curtis et al reported a multistep procedure based on a tandem Diels–Alder/retro-Diels–Alder cycloaddition which allowed to achieve CBG in very high yield (81%) ( Scheme 12 ) [ 113 ].…”
Section: Production Of Phytocannabinoids: From Biosynthesis To Synthe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Like for CBC, the most recent synthetic procedures for preparing CBG have been reported in the year 2021. The group of Curtis et al reported a multistep procedure based on a tandem Diels–Alder/retro-Diels–Alder cycloaddition which allowed to achieve CBG in very high yield (81%) ( Scheme 12 ) [ 113 ].…”
Section: Production Of Phytocannabinoids: From Biosynthesis To Synthe...mentioning
confidence: 99%
“…Following an overview scheme ( Scheme 26 ) showing the synthetic procedures selected by us as the most convenient in terms of yields to obtain CBC (purple route) [ 103 ], CBD (pink route) [ 108 ] and CBG (amaranth route) [ 113 ]. Note that, while the synthetic paths leading to CBC and CBD are both one step processes shearing olivetol as reagent, that leading to CBG is a complicate multi-step process, using reagents completely different from those leading to CBC and CBD.…”
Section: Production Of Phytocannabinoids: From Biosynthesis To Synthe...mentioning
confidence: 99%
“…(Fabaceae family) and the fruit of bastard indigobush, Amorpha fruticosa L. (Fabaceae family), are significant sources of amorfrutins, the active ingredients with a cannabinoid backbone as shown in Table 3 [ 44 , 63 ]. The cannabinoid structures carry an aralkyl side chain, providing facile access to resorcinol precursors of cannabinoids, and are thus categorised as prenylated bibenzyls [ 8 , 64 ]. These amorfrutins are clinically proven to have antidiabetic and lipid-lowering potentials [ 63 , 65 ].…”
Section: Non-cannabis Sourcesmentioning
confidence: 99%
“…These amorfrutins are clinically proven to have antidiabetic and lipid-lowering potentials [ 63 , 65 ]. In animal studies, the natural forms of amorfrutin A and B increased insulin production by targeting the peroxisome proliferator-activated receptor gamma (PPARγ), regulating fat and glucose metabolism, and further down streaming the inflammation [ 64 ]. The terpenolic component and active system for cannabinoid biosynthesis along with the m/z value of the cannabidiol-like structure had also been detected in the flax plant, Linum usitatissimum Linn.…”
Section: Non-cannabis Sourcesmentioning
confidence: 99%
“…Due to these extraordinary biological properties and the predictable application prospects, amorfrutin A and B have attracted the concern of medicinal and synthetic chemists. To date, about thirteen total syntheses of 1 [7,9–10] and seven total syntheses of 2 [8a,9,10i–k,11] have already been reported. Based on the methods of generating the core structure these methods can be categorized into three types including: (a) Using benzoic acid derivatives as raw materials and employing HWE reaction, [10a,h] Sonogashira coupling, [7] Julia olefination [10d] or transition metal‐catalyzed olefination [10e] as a key step for the fabrication.…”
Section: Introductionmentioning
confidence: 99%